2019
DOI: 10.1021/acs.joc.9b00468
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Diylideneisoindolines: Synthesis, Structure, Redox, and Optical Properties

Abstract: Diiminoisoindoline (DII) is a crucial reagent for the synthesis of phthalocyanine as well as related macrocycles and chelates such as hemiporphyrazine and bis(iminopyridyl)isoindoline. In this report, we present the synthesis and characterization of four 1,3-diylideneisoindolines prepared via the reaction of several organic CH acids and DII. These orange or red compounds exhibit intense π → π* transitions in the UV−visible region. The redox properties and electronic structures of all new compounds were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Following our recent findings on the condensation of DII with organic CH-acids that resulted in the formation of 1,3-bis-alkylidene-isoindole-based chromophores, , we decided to explore the reactivity of the phthalonitrile 1 toward other carbon-centered nucleophiles. As the CH-acid precursors, we chose a series of aromatic ketones (acetophenones) 2a–c which can generate nucleophilic enolates upon treatment with a strong base.…”
Section: Resultsmentioning
confidence: 99%
“…Following our recent findings on the condensation of DII with organic CH-acids that resulted in the formation of 1,3-bis-alkylidene-isoindole-based chromophores, , we decided to explore the reactivity of the phthalonitrile 1 toward other carbon-centered nucleophiles. As the CH-acid precursors, we chose a series of aromatic ketones (acetophenones) 2a–c which can generate nucleophilic enolates upon treatment with a strong base.…”
Section: Resultsmentioning
confidence: 99%
“…It was well known that base- or acid-catalyzed self-condensation of 1,3-indanedione afforded several Oligomers, such as dimers of 1,3-indanedione (bindone) and cyclotrimers of 1,3-indanedione (truxenone), etc . Both bindone and truxenone derivatives have been recognized as potential motifs for many polymer materials, such as semiconductors and nonlinear optical and organic photovoltaic materials . The easily in situ generated bindone has multiple reactive sites, which can be employed as reactive synthons for the convenient construction of various indanone-containing polycyclic scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…For the synthesis of diverse indanone-containing polycyclic compounds, 1,3-indanediones are useful candidates because they have three contiguous electrophilic and nucleophilic reactive sites in the cyclic 1,3-dicarbonyl scaffold. More interestingly, the base- or acid-catalyzed self-condensation of 1,3-indanedione afforded the reactive dimer of 1,3-indanedione (bindone) and the cyclotrimer of 1,3-indanedione (truxenone) as well as other oligomers according to the reaction conditions . Both bindone and truxenone are useful scaffolds for various polymer materials such as nonlinear optical, organic photovoltaics, and semiconductors. , On the other hand, the facile base-catalyzed Knoevenagel condensation of 1,3-indanedione with aromatic aldehydes afforded more reactive dipolarophilic 2-arylidene-1,3-indanediones, which were widely employed in many Michael addition, Diels–Alder, annulation, and versatile transformation reactions. Recently, we successfully found that the triethylamine-promoted reaction of 1,3-indanedione with 3-arylideneindolin-2-ones in ethanol gave carbamato-substituted indeno­[1,2- a ]­fluorenes, in which the bindone was in situ generated and underwent a further domino reaction process . However, the similar triethylamine-mediated reaction of 1,3-indanedione with 3-phenacylideneoxindoles afforded triindanone-fused spiro­[bicyclo[2.2.2]­octane-2,3′-indoline] derivatives, in which a truxenone derivative was initially formed, and sequentially, the [4 + 2] cycloaddition reaction proceeded. , These reactions clearly indicated that 1,3-indanedione and its oligomers showed diverse reactivity in cycloaddition reaction and that various complex polycyclic compounds can be conveniently synthesized by using readily available starting materials .…”
Section: Introductionmentioning
confidence: 99%